Locus coeruleus–amygdala circuit disrupts prefrontal control to impair fear extinction - Hugo Bayer; Annalise N. Binette; Samantha O. Sweck; Vitor A. L. Juliano; Samantha L. Plas; Lara M. Ferst; James E. Hassell; Flávio A. G. Mourão; Stephen Maren (Proceedings of the National Academy of Sciences, 2026)
Stress undermines extinction learning and hinders exposure-based clinical therapies for a variety of neuropsychiatric disorders. In both animals and humans, dysfunction in the ventromedial prefrontal cortex (vmPFC) contributes to stress-impaired extinction, but the neural circuit by which stress modulates vmPFC function is not known. We hypothesize that locus coeruleus (LC) norepinephrine undermines extinction learning by recruiting projections from the basolateral amygdala (BLA) to vmPFC. Using a combination of circuit-specific chemogenetics and calcium imaging, we find that activation of LC noradrenergic neurons mimics a behavioral stressor (footshock), induces freezing behavior, reduces spontaneous neuronal activity in the vmPFC, impairs extinction learning, and alters the population dynamics of vmPFC ensembles. Activation of LC also increases shock-induced responses in BLA neurons that project to vmPFC. Selective chemogenetic activation of LC→BLA projections impairs extinction; propranolol infusions into the BLA mitigate the effects of LC activation. Together, these results indicate that the BLA serves as a critical interface between the LC and mPFC to mediate stress-induced extinction impairments.